New interchange : 1B - Richards, Jack C.; Hull, Jonathan, jt. aut.; Proctor, Susan, jt. aut. (Cambridge, U.K. ; New York : Cambridge University, 1997)
Student's audio CD 1B
DDC428.24
Keywords: English language (audio file).; Communication, International -- Problems, exercises, etc